WORLD LITERATURE IN THE LATE XIX AND XX CENTURIES - Ergasheva Marjona (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article is about world literature in the XIX-XX centuries.In addition you learn about writers and their works this period. There are postmoderenism, postcolonialism,and New Sincerity are the major international literary movements of the late 20th century. Each of these movements writers across the globe who share a certain ethos or attitude about truth and the role of literature in society.